“I am alive because of her”: factors affecting adherence to combination antiretroviral therapy among people living with HIV in KwaZulu-Natal, South Africa - Marian Loveday; Jennifer Furin; Sindisiwe Hlangu; Tasneem Naidoo (BMC Infectious Diseases, 2022)
Abstract Background People living with HIV need to take lifelong, combination antiretroviral therapy (cART), but there have been only limited explorations of how factors affecting adherence can change over the course of an individual’s lifetime. Methods We carried out a qualitative study of men and women living with HIV in KwaZulu, Natal, South Africa who were prescribed cART and who had periods of higher and lower adherence. Results 18 individuals participated in open-ended interviews. Using a dynamic theory of adherence, we identified factual, relational, and experiential factors that were associated with adherence and non-adherence to cART. Periods of non-adherence were commonly reported. Participants described relationships and experiences as being important influences on their ability to adhere to cART throughout their treatment journeys. Conclusions Periods of non-adherence to cART are common. While many cART counseling models are based on conveying facts to people prescribed cART, providing opportunities for supportive relationship where people can process their varied experiences is likely important to maintaining health for people living with HIV.